A rare earth metal-based medical rubber material that prevents sharp weapon damage
Through the introduction of rare earth metal base filling materials in the medical rubber material, the problem of insufficient anti -piercing ability of traditional materials has been solved, and higher penetration resistance and better protection effect are achieved.
Patent Information
- Application Number
- CN202411614541.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
Traditional medical rubber materials have limited protective effects in preventing damage to sharp tools, and they tend to age and become brittle after long-term use, reducing their protective performance.
Use rare earth metal base filling materials to prepare in alkaline environments through rare earth nitrate compounds, citric acid, and polymer ligands to form a rare earth metal base filling material with a layer structure, and to nanomate and uniformly disperse them. Go to the rubber material.
It has significantly improved the anti -piercing ability and puncture resistance of medical rubber materials, extended the service life of the material, provided better protection effects, and reduced the impact damage of the puncture power on human tissue.
Smart Images

Figure CN119119573B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical devices, and in particular relates to a rare earth metal-based medical rubber material capable of preventing injury from sharp objects. Background Art
[0002] In the medical field, medical staff often face various risks, one of the biggest risks being cut by sharp medical instruments. This injury not only causes harm to the medical staff's body, but may also lead to the spread of disease. Therefore, it is particularly important to develop a medical rubber material that can effectively prevent injuries from sharp objects. Traditional medical gloves are mainly made of natural rubber, synthetic rubber or PVC. Although they can provide basic protection, their protective effect against puncture and cutting injuries from sharp objects is limited and has a certain degree of limitations. In addition, these materials are prone to aging and becoming brittle after long-term use, reducing their protective performance.
[0003] Rare earth elements have many unique physical and chemical properties due to their special electronic structure. After being modified by some chemical means, some rare earth compounds have high hardness and toughness, which makes them ideal for enhancing the gloves' ability to resist cutting and puncture. In addition, rare earth materials also have good biocompatibility and will not cause allergies or other adverse reactions.
[0004] There are also rubber materials with rare earth materials. As a new type of functional rubber material, rare earth elements can be introduced by melt blending, bonding coordination or in-situ polymerization. It is a practical, simple, easy to prepare and easy to realize composite process. The blending methods are mainly mechanical and melting. In addition, there are methods of dissolving with solvents or solvents. The filling materials can be rare earths and their oxides and modified rare earth organics. The rubber material after the introduction of rare earth materials can obtain better mechanical properties, increase the high-performance load accumulation at the sharp edge of the sharp weapon, improve the tensile mechanical properties of the rubber and the anti-puncture performance of the material, and has excellent properties such as high strength, high modulus, high temperature resistance and good chemical stability. In addition, rare earth functional nanofillers not only effectively prevent sharp weapon injuries during surgery, but also effectively protect medical staff while also having a positive effect on the health of patients.
[0005] Therefore, as an emerging technology in the field of medical devices, rare earth metal-based medical rubber materials that are resistant to injuries from sharp objects have demonstrated great application value and development potential. Summary of the invention
[0006] In view of this, the present invention aims to overcome the defects in the prior art and propose a rare earth metal-based medical rubber material that is resistant to injury by sharp objects.
[0007] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0008] In a first aspect, the present invention provides a rare earth metal-based filling material, which is prepared by co-precipitation of a rare earth nitrate compound, citric acid, and a polymer ligand under an alkaline environment, wherein the mass ratio of the citric acid to the rare earth nitrate compound is 1:(10-15).
[0009] Preferably, the rare earth nitrate compound includes one or a mixture of two or more of lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, gadolinium nitrate hexahydrate, and yttrium nitrate hexahydrate.
[0010] Preferably, the polymer ligand is selected from polyethylene glycol, polyvinyl alcohol, polyether or a mixture of several thereof.
[0011] Preferably, the mass ratio of the citric acid to the polymer ligand is 2:1.
[0012] In a second aspect, the present invention also provides a method for preparing the above-mentioned rare earth metal-based filling material, comprising the following steps:
[0013] S1: adding a citric acid solution dissolved in a polymer ligand to an aqueous solution of a rare earth nitrate hexahydrate, and stirring at 60-80° C. for 2-6 hours to obtain a mixed solution;
[0014] S2: adding alkaline solution to the mixed solution, and after the addition is completed, continuing to stir at 60-80° C. for 2-6 hours to obtain a precursor reaction solution;
[0015] S3: The precursor reaction liquid is dried and concentrated to a dry sample, and then ground, and then calcined at 600-1200° C. to obtain a rare earth metal-based filling material.
[0016] Preferably, the rare earth nitrate compound accounts for 0.4-0.7 mol / L in the mixed solution.
[0017] Preferably, the alkaline solution is aqueous ammonia with a mass concentration of 25%.
[0018] In a third aspect, the present invention also provides a medical rubber material prepared using the above rare earth metal-based filling material.
[0019] In a fourth aspect, the present invention further provides a method for preparing the above-mentioned medical rubber material, comprising the following steps:
[0020] The natural rubber latex, the nano rare earth suspension slurry and the additives are uniformly mixed and then melted and kneaded to obtain a dipping solution, and the suspended mold is immersed in the dipping solution. After keeping for 1-2 hours, the mold is dried to obtain a rare earth metal-based medical rubber material. The nano rare earth suspension slurry is obtained by mixing a rare earth metal-based filling material with ethylene glycol and a dispersant and sand-milling.
[0021] Preferably, the particle size of the rare earth metal-based filling material in the nano rare earth suspension slurry is 100-200 nm.
[0022] Preferably, the solid content of the nano rare earth suspension slurry is 25%-35%.
[0023] Preferably, the added mass of the rare earth metal-based filling material in the natural rubber latex is 1%-2%.
[0024] Preferably, the dispersant is HH2120 water-oil universal dispersant.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] (1) The present invention uses lamellar structure modified rare earth oxide as the introduction of rare earth metal-based filling materials to improve the puncture resistance of medical rubber materials. Compared with traditional medical rubber materials, the use of this material has significantly improved the puncture resistance of the product;
[0027] (2) The modified rare earth metal-based filler material with a lamellar structure prepared by the present invention is transformed into nano-scale small particles with a particle size distribution of about 100-200 nm by a wet sand grinding process, and an auxiliary agent such as 2120 dispersant is used to make the rare earth metal-based filler material uniformly and stably dispersed in the rubber latex, so that it is uniformly dispersed in the rubber material for vulcanization molding;
[0028] (3) The rare earth ions in the present invention have rich electronic energy levels and strong complexing ability. After being assembled into a lamellar structure by chemical means, they are added to the medical rubber material and surface waves are generated by the layered interface, which helps to improve the load concentration state and disperse the impact force, thereby providing better protection effect and helping to reduce the impact damage of penetrating objects to human tissues. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM scanning electron microscope of the rare earth metal-based filling material CALO;
[0030] Figure 2 To test the puncture force / thickness performance of medical rare earth gloves. DETAILED DESCRIPTION
[0031] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0032] The invention provides a rare earth metal-based filling material, which is prepared by a coprecipitation method of a rare earth nitrate compound, citric acid and a polymer ligand under an alkaline environment, wherein the mass ratio of the citric acid to the rare earth nitrate compound is 1:(10-15).
[0033] Preferably, the rare earth nitrate compound includes one or a mixture of two or more of lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, gadolinium nitrate hexahydrate, and yttrium nitrate hexahydrate.
[0034] Preferably, the polymer ligand is selected from polyethylene glycol, polyvinyl alcohol, polyether or a mixture of several thereof.
[0035] Preferably, the mass ratio of the citric acid to the polymer ligand is 2:1.
[0036] The present invention also provides a method for preparing the above rare earth metal-based filling material, comprising the following steps:
[0037] S1: adding a citric acid solution dissolved in a polymer ligand to an aqueous solution of a rare earth nitrate hexahydrate, and stirring at a temperature of 60-80° C. for 2-6 hours to obtain a mixed solution, wherein the polymer ligand is selected from one or a mixture of polyethylene glycol, polyvinyl alcohol, and polyether;
[0038] S2: Add alkaline solution to the mixed solution, and after the addition is completed, continue to maintain 60-80°C and stir for 2-6 hours to obtain a precursor reaction solution; preferably, the alkaline solution is ammonia water with a mass concentration of 25%. By slowly adding alkaline solution to precipitate, a nanoparticle dispersion containing rare earth elements is obtained under precise pH adjustment, thereby controlling the morphology and size of the material.
[0039] S3: The precursor reaction liquid is dried and concentrated to a dry sample, then ground, and then calcined at 600-1200°C to obtain a lamellar rare earth metal-based filling material. The purpose of high-temperature calcination is to remove excess organic matter and impurities.
[0040] Preferably, the rare earth nitrate compound accounts for 0.4-0.7 mol / L in the mixed solution.
[0041] The present invention also provides a method for preparing the above-mentioned medical rubber material, comprising the following steps:
[0042] The natural rubber latex, nano rare earth suspension slurry and additives are evenly mixed and melted to obtain a dipping solution, and the suspended mold is immersed in the dipping solution. The dipping solution is ensured to be completely and evenly attached to the mold by continuous movement. After continuous movement for 1-2 hours, the mold is dried and hardened. The moisture inside the rubber material can also be evaporated by infrared rays to make the rubber material dry. The hardened and dried mold is cleaned to remove impurities, and further dried. After drying, the rubber material on the mold is removed to finally obtain a rare earth metal-based medical rubber material. The nano rare earth suspension slurry is obtained by sand grinding a rare earth metal-based filling material, ethylene glycol and a dispersant.
[0043] Preferably, the particle size of the rare earth metal-based filling material in the nano rare earth suspension slurry is 100-200 nm.
[0044] Preferably, the solid content of the nano rare earth suspension slurry is 25%-35%.
[0045] Preferably, the added mass of the rare earth metal-based filling material in the natural rubber latex is 1%-2%.
[0046] Preferably, the dispersant is HH2120 water-oil universal dispersant.
[0047] The present invention will be described in detail below with reference to the embodiments.
[0048] Example 1
[0049] (1) Preparation of CALO, a rare earth metal-based filler material with a lamellar structure, the specific operation is as follows:
[0050] Weigh 800 g of lanthanum nitrate hexahydrate and add it to 3.2 L of deionized water, then add 60 g of citric acid and 30 g of polyethylene glycol, raise the temperature to 80 °C, install a mechanical stirrer above the reaction container, and continue stirring for 1.5 h, then measure 500 mL of 25% ammonia water and pour it into a constant drop funnel, clamp it above the reaction container, control the ammonia drop speed to 1-2 drops per second, and after all the ammonia water has been added, continue to maintain 80 °C and stir for 0.5 h to obtain a precursor reaction solution.
[0051] The precursor reaction liquid was concentrated to a dry sample in an oven at 110°C, ground into powder in a mortar, and then calcined in a muffle furnace at 1200°C to obtain a rare earth metal-based filler material CALO (CALO for short) with a nanosheet structure.
[0052] (2) CALO wet sand milling to prepare nano rare earth suspension slurry, the specific operation is as follows:
[0053] The obtained rare earth metal-based filler material CALO was added with deionized water and HH2120 water-oil universal dispersant at a solid content of 35%, and then wet sand milled using a NETZSCH MINIFER sand mill with a single machine circulation process. The main machine speed was 3100 rpm, and the sand milling was performed for 6-10 hours to obtain a nano rare earth suspension slurry (referred to as CALO slurry) with a particle distribution of about 100-200nm.
[0054] 1 mL of CALO slurry was taken and diluted 10 times with deionized water, then 1-2 drops of the diluted liquid were taken and dropped on the silicon wafer, which was placed in an oven and dried at 80°C. Then the surface was sprayed with gold and scanned by SEM. The results are as follows: Figure 1 shown.
[0055] From the SEM scan of CALO slurry, it can be seen that CALO is a lamellar stacking structure with a smooth lamellar surface and a thickness of about 300 nm. After being added into the rubber latex with a dispersant, the lamellar CALO is evenly dispersed on the rubber surface, which can absorb and dissipate the energy of the shock wave, thereby reducing the load concentration caused by the puncture force.
[0056] (3) Preparation of rare earth stab-proof medical gloves. The specific operations are as follows:
[0057] Add 5% by mass of dispersant and 5% by mass of curing agent as auxiliary agents to the natural rubber latex and mix them in proportion, then add 2% by mass of CALO slurry and continue to stir evenly. Pour the mixed solution into a rubber mixer, raise the temperature to 130°C, perform melt mixing, then hang the glove mold and immerse it in the dipping solution. After continuous movement for 1 hour, transfer the dipped glove mold to a drying workshop for drying and hardening, and use infrared rays to dry the gloves. Clean the hardened and dried glove mold, remove impurities, and further dry it. After drying, remove the latex gloves on the mold to obtain rare earth metal-based medical rubber gloves that can prevent sharp injuries.
[0058] Example 2
[0059] The difference from Example 1 is that the rare earth nitrate compound is cerium nitrate hexahydrate, the added amount of cerium nitrate hexahydrate is 555.8 g, the added amount of citric acid is 55.6 g, and the added amount of polyethylene glycol is 27.8 g, thereby obtaining a rare earth metal-based filling material CACO.
[0060] Example 3
[0061] The difference from Example 1 is that the rare earth nitrate compound is gadolinium nitrate hexahydrate, and the added amount of gadolinium nitrate hexahydrate is 722.2 g, thereby obtaining a rare earth metal-based filling material CAGO.
[0062] Example 4
[0063] The difference from Example 1 is that the rare earth nitrate compound is yttrium nitrate hexahydrate, and the added amount of yttrium nitrate hexahydrate is 857.9 g, thereby obtaining a rare earth metal-based filling material CAYO.
[0064] Example 5
[0065] The difference from Example 1 is that polyethylene glycol is replaced by polyvinyl alcohol, the added amount of citric acid is 53.3 g, and the added amount of polyethylene glycol is 26.7 g, to obtain a rare earth metal-based filling material CALO-A.
[0066] Example 6
[0067] The difference from Example 1 is that polyethylene glycol is replaced by polyether to obtain the rare earth metal-based filling material CALO-B.
[0068] Comparative Example 1
[0069] The difference from Example 1 is that the added amount of citric acid is changed to 40 g, and the added amount of polyethylene glycol is changed to 20 g, thereby obtaining a rare earth metal-based filling material CALO-1.
[0070] Comparative Example 2
[0071] The difference from Example 1 is that the added amount of citric acid is changed to 160 g, and the added amount of polyethylene glycol is changed to 80 g, thereby obtaining a rare earth metal-based filling material CALO-2.
[0072] Comparative Example 3
[0073] The difference from Example 1 is that the amount of deionized water added is changed to 6 L, and a rare earth metal-based filling material CALO-3 is obtained.
[0074] Comparative Example 4
[0075] The difference from Example 1 is that the amount of deionized water added is changed to 2.4 L, and a rare earth metal-based filling material CALO-4 is obtained.
[0076] Comparative Example 5
[0077] The difference from Example 1 is that the alkaline solution is a sodium hydroxide aqueous solution with a mass concentration of 25%, and a rare earth metal-based filling material CALO-5 is obtained.
[0078] Test Example 1: Puncture force / thickness index test of rare earth metal-based medical rubber gloves to prevent sharp weapon injury
[0079] The gloves prepared in Examples 1 to 6 and Comparative Examples 1 to 5 to be tested were cut into sample pieces with a diameter of 100 mm, and named CALO rubber, CACO rubber, CAGO rubber, CAYO rubber, CALO-A rubber, CALO-B rubber, CALO-1 rubber, CALO-2 rubber, CALO-3 rubber, CALO-4 rubber, and CALO-5 rubber in sequence, and then clamped in the upper and lower clamps of a universal mechanical testing machine, respectively. The puncture needle and sample clamp were installed, and the equipment parameters were adjusted to set the speed for puncturing the sample. Three groups of experimental tests were conducted in parallel, and the thickness of the experimental rubber samples was tested simultaneously. The puncture force / thickness results were calculated, and the average value was taken as the puncture resistance of the gloves. The results are as follows: Figure 2 shown.
[0080] Figure 2 It can be seen that CALO rubber has the highest puncture force / thickness index. Compared with ordinary rubber, the puncture force / thickness index can be increased from 18.97 N / mm to 31.07 N / mm, and the performance improvement reaches 63.8%. This means that CALO rubber has a stronger puncture resistance and can be used as a rubber filler in medical puncture-resistant gloves. The puncture force / thickness index of CACO rubber, CAGO rubber, CAYO rubber, CALO-A rubber, and CALO-B rubber are not as good as the performance of CALO rubber. The performance of CALO-1 rubber, CALO-2 rubber, CALO-3 rubber, CALO-4 rubber, and CALO-5 rubber has all declined, proving that the five rare earth metal-based filling materials CALO-1, CALO-2, CALO-3, CALO-4, and CALO-5 are not suitable for use as filling materials in rubber.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A rare earth metal-based filling material, characterized in that: It is prepared by co-precipitation of rare earth nitrate compounds, citric acid and polymer ligands in an alkaline environment, wherein the mass ratio of citric acid to rare earth nitrate compounds is 1:(10-15); The rare earth nitrate compound includes one or a mixture of two or more of lanthanum nitrate hexahydrate, cerium nitrate hexahydrate, gadolinium nitrate hexahydrate, and yttrium nitrate hexahydrate; The polymer ligand is selected from polyethylene glycol and / or polyvinyl alcohol; The mass ratio of the citric acid to the polymer ligand is 2:1; The method for preparing the rare earth metal-based filling material comprises the following steps: S1: adding a citric acid solution dissolved in a polymer ligand to an aqueous solution of a rare earth nitrate hexahydrate, and stirring at 60-80° C. for 2-6 hours to obtain a mixed solution; S2: adding alkaline solution to the mixed solution, and after the addition is completed, continuing to stir at 60-80° C. for 2-6 hours to obtain a precursor reaction solution; S3: drying and concentrating the precursor reaction liquid to a dry sample, grinding it, and then calcining it at 600-1200° C. to obtain a rare earth metal-based filling material; the rare earth nitrate compound accounts for 0.4-0.7 mol / L in the mixed solution; The alkaline solution is aqueous ammonia with a mass concentration of 25%.
2. A medical rubber material prepared using the rare earth metal-based filling material according to claim 1.
Citation Information
Patent Citations
Preparation method of nano rare earth oxide and nano rare earth oxide
CN114436312A
Preparation method and application of lanthanide series metal oxide nanosheet
CN115594211A